A simple method to produce birnessite‐coated quartz sand. Issue 4 (7th July 2017) - Georgiadis, Anna; Rennert, Thilo
Abstract: Birnessite is a highly reactive manganese oxide and common in soil. We checked the attachment of birnessite, synthesized by the reduction of permanganate by lactate, on sand‐sized quartz to produce birnessite‐coated sand (BCS). Attachment and aggregation of birnessite increased with pH and reaction time. The extent of Cu and Zn adsorption to BCS was similar to that of birnessites in previous studies. Based on these results and the stability of this BCS, it may be used in water treatment.